Additional Stress on a Buried Pipeline under the Influence of Coal Mining Subsidence - Ping Xu; Minxia Zhang; Zhibin Lin; Zhengzheng Cao; Xu Chang (Advances in Civil Engineering)
Buried pipelines influenced by coal mining subsidence will deform and generate additional stress during surface deformation. On the basis of the coordinating deformation relationship between buried pipeline and its surrounding soils, a stress analysis method of a buried pipeline induced by mining was proposed. The buried pipeline additional stresses were analyzed; meanwhile, a corresponding analysis process of the pipeline stresses was also presented during mining subsidence. Furthermore, based on the ground subsidence along the pipeline predicted in advance by the probability integral method, the additional stresses and Von Mises equivalent stresses and their distributions along the buried pipeline induced by the exploitation of a coal mining working face named 14101 were obtained. Meanwhile, a comparative analysis of additional stresses between simulation and analytical calculation was performed for the deep analysis and reliability of the results presented by the proposed methodology in this paper. The proposed method provides references for analysis of the additional stress and safety of buried pipelines under the influence of mining subsidence.